Effect of Mirror Therapy Versus Cognitive Therapeutic Exercise on Upper Limb Functionality, Autonomy, and Poststroke Quality of Life: A Randomized Trial. - Fernández-Solana, Jessica; Vélez-Santamaría, Rodrigo; Moreno-Villanueva, Adrián; Álvarez-Pardo, Sergio; González-Bernal, Jerónimo; Santamaría-Peláez, Mirian; González-Santos, Josefa (American Journal of Occupational Therapy)
Importance: A combination of rehabilitation techniques may be useful to optimize individualized treatment and efficient resource utilization. Objective: To assess the effect of cognitive therapeutic exercise (CTE) and mirror therapy (MT) combined with task-oriented training (TOT) on upper limb functionality, fine and gross motor skills, use of the paretic arm, functional independence in activities of daily living (ADLs), and quality of life among people with subacute stroke. Design: Randomized trial, longitudinal, and multicenter study with one control group (CG) and two experimental groups (EGs) who were assessed before, after, and 3 mo posttreatment. Setting: University of Burgos and Burgos University Hospital, Burgos, Spain. Participants: One hundred twenty patients with subacute stroke and motor symptoms in the upper limb recruited through consecutive nonprobabilistic sampling and excluding those with tremor due to another neurological disease or cognitive impairment. Intervention: MT + TOT (EG1) and CTE + TOT (EG2) over 20 1-hr sessions. T3he CG received usual therapy (TOT) that simulated everyday situations. Outcomes and Measures: The studied variables were evaluated with the Action Research Arm Test, Box and Block Test, Motor Activity Log, FIM™–Functional Assessment Measure, and Stroke-Specific Quality of Life Scale. Results: Statistically significant differences were found between the CG group and both EGs, with improvements in upper limb functionality, fine and gross motor skills, use of the paretic arm, functional independence in ADLs, and quality of life. No differences were found between EGs. Conclusions and Relevance: Application of these combined interventions improved all variables studied. Plain-Language Summary: This study found that the use of cognitive therapeutic exercise and mirror therapy combined with task-oriented training may improve upper limb functionality, fine and gross motor skills, the use of the paretic arm, functional independence in activities of daily living, and quality of life among people with subacute stroke. The authors assess the effect of cognitive therapeutic exercise and mirror therapy combined with task-oriented training for people with subacute stroke.